Internal jugular vein cannulation: A comparison of three techniques - Bikash R Ray; Virender K Mohan; Lokesh Kashyap; Dilip Shende; Vanlal M Darlong; Ravindra K Pandey (Wolters Kluwer Medknow Publications, 2013)
Context: Ultrasound-guided internal jugular vein (IJV) cannulation is known for increasing success rate and decreasing rate of complications. The ultrasound image can be used as a real time image during cannulation or to prelocate the IJV before attempting cannulation. Aims: This study compares both the ultrasound-guided technique with the classical anatomical landmark technique (central approach) for right IJV cannulation in terms of success rate, complications, and time for cannulation. Settings and Design: A prospective, randomized, observational study was conducted at a tertiary care hospital. Material and Methods: One hundred twenty patients requiring IJV cannulation were included in this study and were randomly allocated in three groups. Number of attempts, success rate, venous access time, catheterization time, and complications were observed in each group. Statistical Analysis Used: Statistical analysis was performed using STATA-9 software. Demographic data were compared using one-way analysis of variance (ANOVA). Nonparametric data were compared using the Kruskall-Wallis test, and multiple comparisons were done applying The Mann-Whitney test for individual pairs of groups. Nominal data were compared by applying the Chi-square test and Fisher exact test. Results: Successful cannulation (≤3 attempt) was achieved in 90.83% of patients without any statistical significant difference between the groups. Venous access time and catheterization time was found to be significantly less in both the ultrasound groups than the anatomical land mark group. Number of attempts and success in first attempt was similar between the groups. Conclusions: Both the ultrasound techniques are found to be better than the anatomical landmark technique. Further, ultrasound-guided prelocation was found to be as effective as ultrasound guided real-time imaging technique for right IJV cannulation.